Record of polycyclic aromatic hydrocarbons (PAHs) from prehistoric sediments and human activity in the Lubei plain of China - Huanrong Zuo; Zhihai Tan; Yongming M Han; Longjiang Mao; Shuxin Zheng; Qi Zhang; Meng Wang; Shihao Li (Scientific Reports)
Abstract Understanding the sources and dynamics of past biomass burning remain a significant challenge due to variations in paleofire combustion patterns across different temporal and spatial scales. This study integrates black carbon and polycyclic aromatic hydrocarbon (PAH) records from the Lubei Plain in the Shandong Peninsula, Lower Yellow River, to reconstruct Holocene fire regimes and their relationship with climatic shifts and human activities over the past 5000 years. During the mid-to-late Holocene (5000–3000 year BP. (calendar years before 1950)), a biomass burning levels were generally low, with a pronounced peak in low-molecular-weight PAHs (3-ring PAHs) and charcoal fluxes between 5000 and 4500 year BP, indicating increased fire activity likely driven by a short-term cold-dry event around 5000 year BP. From 3500 to 1000 year BP, three distinct episodes of low-temperature smoldering fires are identified, coinciding with deforestation and persistent droughts during the Shang Dynasty (3600–3046 year BP), the Qin and Western Han Dynasties (2200–2000 year BP), and the Sui and Tang Dynasties (1400–1100 year BP). In contrast, high-temperature flaming fires are associated with periods of intensified warfare and social upheaval, compounded by cold, arid climates during the Warring States period (2500–2400 year BP), the Eastern Han Dynasty (2000–1800 year BP), and the Wei, Jin, and Southern-Northern Dynasties (1800–1400 year BP). Over the past millennium, anthropogenic biomass burning remained elevated, reflecting sustained human influence on fire regimes. Meanwhile, Pollen and n-alkane records reveal a transition from primary forests to secondary shrubland during the late Holocene, driven by declining seasonal precipitation linked to a weakening East Asian monsoon and increased anthropogenic burning. Principal component analysis indicates that long-term deforestation primarily drove low-temperature smoldering fires, whereas high-temperature fires were more closely linked to periods of conflict. Seasonal precipitation variability, regulated by monsoonal dynamics, emerged as a fundamental control on fire regimes. This integrated analysis of PAHs, black carbon, and charcoal, coupled with multivariate statistical approaches, offers a robust framework for reconstructing fire-climate-human interactions in East Asia. The findings provide new insights into the mechanisms driving fire regimes and their long-term ecological and societal impacts.